Workshop Merancang Pembelajaran dan Asesmen dalam Implementasi Kurikulum Merdeka bagi Guru SMK Kabupaten Wonosobo - Sukarni, Semi; Sudar, Sudar; Rokhayati, Titi (Abdibaraya, 2023)
The objectives of community service that have been implemented by the English Language Education Master's Study Program service team include: (1) Sharing knowledge about designing English language learning for Phase E & F (SMK) based on the Curriculum Merdeka; (2) Sharing knowledge about appropriate methods, media and materials to be used in learning English based on the Curriculum Merdeka; (3) Sharing knowledge about assessments in accordance with the Merdeka Curriculum English Phase E & F Learning Outcomes; (4) Reviewing teaching modules for learning English for Phase E & F (SMK) based on the Merdeka Curriculum. The service partners are vocational English teachers in the Wonosobo Regency MGMP group which will be held at SMK 2 Wonosobo. Service activities were held in face-to-face meetings and attended by 42 English teachers. This activity was carried out with maximum results with good cooperation between the Community Service Team, the Institute for Research and Community Service (LPPM) Muhammadiyah University Purworejo and all English teachers in the Wonosobo Regency Vocational School English Language MGMP group. Keywords: Asesment, learning design , Merdeka Curriculum, workshop